“To be read absent-mindedly in a Warsaw café” – political satire and humour in the newspaper Nowa Polska, 1831 - Karpińska, Małgorzata (Laughter, humour, satire, 2024)
Nowa Polska, a newspaper with the subtitle “Journal of Politics and Science”, began circulating in Warsaw on 5 January 1831 as an organ of radical circles. Its contributors included Kamil and Maurycy Mochnacki, Ludwik Nabielak and Adam Gurowski. From the very first issue, the paper, which was read in cafés as well as on Warsaw’s streets and squares, engaged in fierce polemics with all other political circles. However, it did not always pursue serious debates or refer to substantive or scientific arguments, as its subtitle suggests. Both the young age of most of its contributors and its audience led the editors to be uncompromising and ruthless in their criticism. Humour was very often the weapon aimed at the adversaries. Political satire, cutting bon mots and even the occasional bawdy mockery were to appeal not only to the intellect but also to the emotions of the readers. They also greatly expanded the readership. This article presents the main trends of satire, the people who became the object of ridicule and the attitudes and decisions that were most often mocked. The type of humour used to discredit political opponents is also analysed.